Locally-enhanced configurable copper-based composite material as well as preparation method and application of locally-enhanced configurable copper-based composite material
By using a specific proportion of casting and seepage additives mixed with nickel oxide, aluminum powder and silicon sol in a copper-based composite material to form a porous preform with ceramic particles, the self-exothermic reaction during casting and seepage is used to regulate the thickness of the reinforced body, and the problem of failure to achieve local regional strength improvement in the prior art is solved, efficient local enhancement effect is achieved and cost is reduced.
Patent Information
- Application Number
- CN202411951992.6
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-12-27
- Publication Date
- 2025-03-11
AI Technical Summary
In specific service environments, such as impact wear or friction wear, existing copper-based composite materials cannot achieve significant improvement in local area strength, and the overall strength improvement method increases costs and causes waste of materials.
By mixing the casting penetration additive obtained by mixing nickel oxide, aluminum powder and silica sol at a specific mass ratio with ceramic particles, a porous preform is formed, and the thickness of the reinforcement is regulated by using the self-exothermic reaction of the casting penetration additive during the casting penetration process to achieve local enhancement.
It achieves a higher demand for local wear resistance under specific working conditions, reduces production costs, and effectively regulates the strengthening effect of the reinforcement body.
Smart Images

Figure CN119592835A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the technical field of copper-based composite material preparation, and in particular relates to a locally enhanced configuration copper-based composite material and a preparation method and application thereof. Background Art
[0002] Copper-based composite materials are a new type of material with special properties. They are based on copper or copper alloys and are made by adding a certain amount of alloying elements or reinforcements, such as carbon fiber, ceramic particles, metal powder, whiskers, fibers, etc., and through mixing, pressing, sintering and other processes. This composite material not only retains the excellent thermal conductivity, electrical conductivity and mechanical properties of copper, but also significantly improves its strength, hardness, wear resistance and corrosion resistance through the addition of reinforcement materials, so that it can still maintain good performance under harsh conditions such as high temperature and high pressure.
[0003] The preparation of reinforcements in copper-based composite materials usually uses in-situ synthesis methods or external addition methods to make the reinforcements evenly dispersed inside and outside the crystals of the copper matrix. In actual service, in some specific service environments, such as impact wear conditions or friction wear conditions, only the local strength of the copper-based composite material is required to be high, and the overall strength does not need to be improved. However, the in-situ synthesis method or the external addition method is to improve the strength of the copper-based composite material as a whole, and the effect of local reinforcement in a specific area is not significant enough, and it will also increase costs and cause material waste. Summary of the invention
[0004] In order to solve the above technical problems, the present invention provides a locally enhanced structured copper-based composite material and a preparation method and application thereof, which can achieve local enhancement and meet the needs of special working conditions.
[0005] To achieve the above objectives, the technical solution of the present invention is as follows.
[0006] The first aspect of the present invention provides a method for preparing a locally enhanced structured copper-based composite material, comprising the following steps:
[0007] The ceramic particles and the casting infiltration aid are mixed in a mass ratio of 0.05 to 0.2:1 to obtain a preform; the casting infiltration aid is composed of nickel oxide aluminum powder and silica sol in a mass ratio of 1:1 to 10:2 to 5;
[0008] The preform is placed in a set cavity area, and copper metal liquid is poured into it for infiltration casting. The thickness of the local reinforcement is regulated by a self-exothermic reaction of the infiltration aid to obtain a locally reinforced structured copper-based composite material.
[0009] The casting infiltration aid obtained by mixing nickel oxide, aluminum powder and silica sol in a mass ratio of 1:1 to 10:2 to 5 can ensure that the nickel oxide aluminum powder and silica sol react completely during the casting infiltration process, providing sufficient heat for regulating the thickness of the reinforcement, thereby meeting the higher demand for local wear resistance under specific working conditions. The ceramic particles are mixed with the casting infiltration aid in a mass ratio of 0.05 to 0.2:1, and the obtained preform has a porous structure, which can ensure that the copper metal liquid is completely cast and infiltrated into the preform. After the copper metal liquid is cast and infiltrated, the local enhanced configuration copper-based composite material is obtained. The organizational structure is different from the traditional integral dispersed copper-based composite material. The organizational structure of the dispersed copper-based composite material is ceramic particles uniformly dispersed on the copper matrix, and each area is reinforced by the reinforcement, but the local reinforcement effect of the reinforcement is not obvious. The method of the present invention can achieve the regulation of the strengthening of the local reinforcement.
[0010] More importantly, the present invention mixes nickel oxide, aluminum powder and silica sol in a specific mass ratio of 1:1 to 10:2 to 5, thereby ensuring that the nickel oxide aluminum powder and silica sol react completely during the casting process to achieve control of the thickness of the reinforcement. If the ratio of nickel oxide, aluminum powder and silica sol is replaced, the above-mentioned corresponding technical effects cannot be achieved.
[0011] In another preferred embodiment, the thickness of the reinforcement is 1 mm to 30 mm.
[0012] In another preferred embodiment, the specific preparation process of the preform is as follows:
[0013] The ceramic particles and the casting and infiltration aid are mixed, poured into a mold, and dried to obtain a preform;
[0014] In another preferred embodiment, the drying temperature is 200°C to 300°C.
[0015] In another preferred embodiment, the temperature of the infiltration casting is 1100°C to 1200°C.
[0016] In another preferred embodiment, the ceramic particles are aluminum oxide or silicon carbide.
[0017] In another preferred embodiment, the particle size of the ceramic particles is 10 μm to 3 mm; micron-sized ceramic particles are used in impact wear conditions, and millimeter-sized ceramic particles are used in friction wear conditions.
[0018] The second aspect of the present invention provides the locally enhanced structured copper-based composite material.
[0019] The third aspect of the present invention provides an application of the locally enhanced structured copper-based composite material in the preparation of marine propellers, aerospace engine turbine pump bearings, high-speed rail pantographs, and aircraft brake pads.
[0020] Compared with the prior art, the present invention has the following beneficial effects:
[0021] The present invention can ensure that nickel oxide, aluminum powder and silica sol react completely during the casting process through the casting infiltration aid, and provide sufficient heat for regulating the thickness of the reinforcement to meet the demand for local reinforcement under specific service conditions. In addition, the preform obtained by mixing the casting infiltration aid with ceramic particles has a porous structure that can ensure that the copper metal liquid is completely cast and infiltrated into the preform. After the copper metal liquid is cast and infiltrated, the locally enhanced configuration copper-based composite material is different from the traditional integral diffuse distribution copper-based composite material. The locally enhanced configuration copper-based composite material in the present invention has the characteristics of regional composite strengthening, and realizes the regulation of the strengthening of the local reinforcement. BRIEF DESCRIPTION OF THE DRAWINGS
[0022] Figure 1 Schematic diagram of the preform in Example 1 of the present invention.
[0023] Figure 2 Schematic diagram of the casting infiltration aid in Example 1 of the present invention. DETAILED DESCRIPTION
[0024] The technical solution of the present invention will be described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.
[0025] In the present invention, unless otherwise specified, all the embodiments and preferred implementation methods mentioned in the present invention can be combined with each other to form a new technical solution.
[0026] The prior art adopts an in-situ synthesis method to prepare reinforcements in copper-based composite materials, and improves the wear resistance of copper-based composite materials by uniformly dispersing the reinforcements inside and outside the crystals of the copper matrix. Among them, the in-situ synthesis method refers to adding ceramic raw materials to copper melt or copper powder raw materials for sintering, and an in-situ chemical reaction occurs during the solidification or sintering process, so that the reinforcements are uniformly dispersed inside and outside the crystals of the copper matrix, thereby achieving the purpose of improving the wear resistance. However, under some special working conditions, such as impact wear conditions or friction wear conditions, it has higher requirements for local wear resistance. Since the reinforcements in the prior art are uniformly dispersed, the purpose of local enhancement cannot be achieved. In order to meet the local enhancement requirements, by preparing excessive reinforcements in the copper-based composite material, the production cost is greatly increased.
[0027] The embodiment of the present invention provides a locally enhanced configuration copper-based composite material and a preparation method and application thereof. The casting infiltration aid obtained by controlling the mass ratio of nickel oxide aluminum powder and silica sol can ensure that the nickel oxide aluminum powder and silica sol react completely during the casting infiltration process, provide sufficient heat, and be used to adjust the thickness of the reinforcement. The greater the heat provided, the slower the solidification of the molten metal, the thicker the molten metal penetrates into the reinforcement, the thicker the reinforcement, and the better the wear resistance, so as to meet the higher demand for local wear resistance under specific working conditions. The mass ratio of ceramic particles to the casting infiltration aid is controlled so that the obtained preform has a porous structure, which can ensure that the copper metal liquid is completely cast and infiltrated into the preform. After the copper metal liquid is cast and infiltrated, the locally enhanced configuration copper-based composite material is different from the traditional integral diffusely distributed copper-based composite material structure. The diffusely distributed copper-based composite material structure is ceramic particles uniformly dispersed on the copper matrix, and each region is reinforced by the reinforcement, but the reinforcement strengthening effect is not obvious; and the method in the present invention can achieve the regulation of the reinforcement strengthening effect to meet the needs of different working conditions.
[0028] The following is a detailed description of a locally enhanced structured copper-based composite material, its preparation method and its application.
[0029] Example 1
[0030] A method for preparing a locally enhanced structured copper-based composite material comprises the following steps:
[0031] S1. Mix nickel oxide, aluminum powder and silica sol in a mass ratio of 1:10:5 to obtain a casting infiltration aid, such as Figure 2 shown.
[0032] S2, silicon carbide with a particle size of 10 μm and a casting infiltration aid are mixed in a mass ratio of 0.2:1, poured into a mold, and dried at 200°C to obtain a preform with a thickness of 28 mm. Figure 1 shown.
[0033] S3. Place the preform in a set cavity area, pour in molten copper, and perform infiltration at 1200°C. The infiltration aid produces a self-exothermic reaction to provide infiltration energy for the silicon carbide area. The molten copper slowly enters the preform to form a local reinforcement with a thickness of 28 mm to 30 mm, thereby obtaining a locally reinforced structured copper-based composite material.
[0034] Example 2
[0035] A method for preparing a locally enhanced structured copper-based composite material comprises the following steps:
[0036] S1. Mix nickel oxide, aluminum powder and silica sol in a mass ratio of 1:1:2 to obtain a casting infiltration aid.
[0037] S2. Alumina with a particle size of 3 mm and a casting infiltration aid are mixed in a mass ratio of 0.2:1, poured into a mold, and dried at 300° C. to obtain a preform with a thickness of 8 mm.
[0038] S3. Place the preform in a set cavity area, pour in molten copper, and perform infiltration at 1100°C. The infiltration aid produces a self-exothermic reaction to provide infiltration energy for the silicon carbide area. The molten copper slowly enters the preform to form a local reinforcement with a thickness of 10 mm to 12 mm, thereby obtaining a locally reinforced structured copper-based composite material.
[0039] Example 3
[0040] A method for preparing a locally enhanced structured copper-based composite material comprises the following steps:
[0041] S1. Mix nickel oxide, aluminum powder and silica sol in a mass ratio of 1:3:5 to obtain a casting infiltration aid.
[0042] S2. Alumina with a particle size of 1 mm and a casting infiltration aid are mixed in a mass ratio of 0.05:1, poured into a mold and dried at 240° C. to obtain a preform with a thickness of 12 mm.
[0043] S3. Place the preform in the set cavity area, pour in molten copper, and perform infiltration at 1130°C. The infiltration aid produces a self-exothermic reaction to provide infiltration energy for the silicon carbide area. The molten copper slowly enters the preform to form a local reinforcement with a thickness of 15 mm, thereby obtaining a locally reinforced structured copper-based composite material.
[0044] Example 4
[0045] A method for preparing a locally enhanced structured copper-based composite material comprises the following steps:
[0046] S1. Mix nickel oxide, aluminum powder and silica sol in a mass ratio of 1:5:8 to obtain a casting infiltration aid.
[0047] S2. Silicon carbide with a particle size of 200 μm and a casting infiltration aid are mixed in a mass ratio of 0.1:1, poured into a mold and dried at 280° C. to obtain a preform with a thickness of 18 mm.
[0048] S3. Place the preform in the set cavity area, pour in molten copper, and perform infiltration at 1180°C. The infiltration aid produces a self-exothermic reaction to provide infiltration energy for the silicon carbide area. The molten copper slowly enters the preform to form a local reinforcement with a thickness of 20 mm, thereby obtaining a locally reinforced structured copper-based composite material.
[0049] The locally reinforced structured copper-based composite materials prepared in Examples 1 to 4 were used as the experimental group, the copper-based composite materials without local reinforcement were used as the control group 1, and the copper-based composite materials prepared by the in-situ synthesis method were used as the control group 2, and friction and wear measurements were performed respectively, and the results are shown in Table 1. The in-situ synthesis method refers to adding ceramic raw materials to copper melt or copper powder raw materials for sintering, and an in-situ chemical reaction occurs during the solidification or sintering process.
[0050] Table 1 Friction and wear test results
[0051]
[0052] From the results in Table 1, it can be seen that the friction coefficient and wear loss of the locally reinforced structured copper-based composite materials in experimental groups 1 to 3 are lower than those in control group 1, and better than those in control group 2.
[0053] From the hardness results, it can be seen that the strength of the reinforcement layer of the locally reinforced structured copper-based composite materials in experimental groups 1 to 3 is different. The hardness of the reinforcement layer parts in the three experimental groups is significantly improved compared with the matrix part, which proves that the method of the present invention can achieve the effect of local enhancement, and the hardness is higher than that of the control group 1, indicating that the method of the present invention can achieve the purpose of local strength enhancement, and then can be applied to special working conditions such as industrial propellers, aerospace engine turbopump bearings, high-speed rail pantographs, aircraft brake pads, etc., to achieve the effect of local enhancement and reduce cost investment.
[0054] The strength of the strengthening layer in the experimental group 1 is the same as that in the control group 2, indicating that the method of the present invention can also achieve the high-strength requirement. It can be seen that the method of the present invention can achieve the effect of local enhancement, effectively reduce the friction coefficient and wear, and thus meet the strength requirements under specific working conditions.
[0055] The flexural strength of the strengthening layer of the experimental group, control group 1 and control group 2 was measured, and the results are shown in Table 2.
[0056] Table 2 Flexural strength results
[0057] Group Bending strength Experimental Group 1 >300MPa Experimental Group 2 >250MPa Experimental Group 3 >270MPa Experimental Group 4 >280MPa Control group 1 <200MPa Control group 2 >300MPa
[0058] From the results in Table 2, it can be seen that the flexural strengths of experimental groups 1 to 3 are all higher than those of control group 1, and are equivalent to those of control group 2. This shows that the locally reinforced structured copper-based composites obtained by local reinforcement still have good flexural strength, and the problem of reduced flexural strength will not occur due to local reinforcement.
[0059] It can be seen from the above experimental results that the casting infiltration aid obtained by mixing nickel oxide aluminum powder and silica sol in a mass ratio of 1:1 to 10:2 to 5 can provide different heat requirements during the casting infiltration process to obtain reinforcements of different thicknesses, thereby achieving local different strength requirements. In addition, the preform obtained by mixing ceramic particles and the casting infiltration aid in a mass ratio of 0.05 to 0.2:1 has a porous structure, which can ensure that the copper metal liquid is completely cast and infiltrated into the preform. After the copper metal liquid is cast and infiltrated, a reinforcement can be formed locally, and the local reinforcement effect is obvious to meet the needs of different working conditions.
[0060] The above are only preferred embodiments of the present invention and are not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principles of the present invention should be included in the protection scope of the present invention.
Claims
1. A method for preparing a locally enhanced structured copper-based composite material, characterized in that: The following steps are involved: The ceramic particles and the casting and infiltration aid are mixed in a mass ratio of 0.05 to 0.2:1 to obtain a preform; the casting and infiltration aid is prepared by mixing nickel oxide, aluminum powder and silica sol in a mass ratio of 1:1 to 10:2 to 5; The preform is placed in the cavity area, and copper metal liquid is poured into it for infiltration casting. The thickness of the local reinforcement is regulated by a self-exothermic reaction of the infiltration casting aid to obtain a locally reinforced structured copper-based composite material.
2. The method for preparing the locally enhanced structured copper-based composite material according to claim 1, characterized in that: The thickness of the local reinforcement is 1 mm to 30 mm.
3. The method for preparing the locally enhanced structured copper-based composite material according to claim 1, characterized in that: The specific preparation process of the preform is as follows: The ceramic particles and the casting and infiltration aid are mixed and dried to obtain a preform.
4. The method for preparing the locally enhanced structured copper-based composite material according to claim 3, characterized in that: The drying temperature is 200°C to 300°C.
5. The method for preparing the locally enhanced structured copper-based composite material according to claim 1, characterized in that: The temperature of the infiltration casting is 1100°C to 1200°C.
6. The method for preparing the locally enhanced structured copper-based composite material according to claim 1, characterized in that: The ceramic particles are aluminum oxide or silicon carbide.
7. The method for preparing the locally enhanced structured copper-based composite material according to claim 6, characterized in that: The particle size of the ceramic particles is 10 μm to 3 mm.
8. A locally enhanced structured copper-based composite material prepared by the preparation method according to any one of claims 1 to 7.
9. An application of the locally enhanced structured copper-based composite material according to claim 8 in the preparation of marine propellers, aerospace engine turbopump bearings, high-speed rail pantographs, and aircraft brake pads.